HOSPITAL MORTALITY OF CARDIAC SURGERY PATIENTS WITH ACUTE KIDNEY INJURY ON RENAL REPLACEMENT THERAPY - К. Zakon; М. Kolesnyk; V. Dudarenko; G. Radchenko (Український Журнал Нефрології та Діалізу, 2014)
The purpose of this study was to compare the influence of different modalities of renal replacement therapy (RRT) on outcome of cardiac surgery patients (pts) with acute kidney injury (AKI).